Професійно-кар'єрний розвиток та самовдосконалення майбутнього інженера засобами інтелектуально-ігрової практики - Ігнатюк, Ольга Анатоліївна (Класичний приватний університет, 2016)
Статтю присвячено проблемі підвищення якості фахової підготовки майбутніх інженерів до професійної діяльності. У центрі уваги перебувають питання визначення сутності і змісту інтелектуально-ігрової практики як засобу професійно-кар’єрного розвитку й самовдосконалення майбутнього інженера. Визначається зміст і сутність етапів проектування моделі професійно значущих якостей майбутніх інженерів, які спрямовані на його професійно-кар’єрний розвиток й самовдосконалення під час фахової підготовки в умовах технічного університету.

The article is devoted to improving the quality of training of future engineers to professional work. The focus artical is on the issues of determining the nature and content and intellectual match practice as a means of professional and career development and self-improvement of the future engineer. The content and nature of the stages of designing a model of professionally significant qualities (PSQ) of future engineers, aimed at his professional career development and self-improvement during training in a technical university. Theoretically and practically socio-pedagogical model of professionally significant qualities of the student's personality in the study of the Technical University of integrated psychological, pedagogical and management disciplines with intellectually-game practice (IGP) are justified. This model is full synchronization of the goals, objectives, trends and methods, conditions for the creation of pedagogically developing environment, diagnostic and structuring. The process of developing the PSQ students occurs efficiently in the simulation of the process of using intellectually-game practice (IGP). The level of PSQ formation is not only a characteristic of the evaluation, but also the identification of creative attitude to their profession. Identify the components of the individual, along with valuable relations, self-awareness, social activity, it acts such basic characteristics as the commitment to the professional activity, the prospects of which, in turn, gives the concept of general simulation of professionally important qualities of the person of the future engineer. Further research should be directed to a detailed study of the problem of formation of the competitive expert at the Technical University, and quality management training future engineers.
Professional career-development and self-improvement of the future engineer of intellectually-game practice
Keywords: дисципліна навчальна; дисципліна інтегрована; фахівець; конкурентоспроможність; студент; особистість; університет технічний; підготовка професійна; integrated academic subjects; competitive specialist; engineer; professional development; career development; professional self-improvement; student; Technical University; professional training